Aspects of the theory and practice of choral training in South African schools - Radue, Robin R (Rhodes University, Faculty of Humanities, Department of Music, 1980)
Firstly, the matter of constituting a choir is discussed. This involves auditioning, with its attendant problems of nervousness and self-consciousness on the part of the children, and assessment on that of the trainer. In the final analysis, after enthusiastically advertising the rewards to be gained from choral singing, and after trying to create an environment which is seen to be conducive to this philosophy, the trainer has to make the best of the willing forces available. Rehearsals are probably more important than performances, since the time devoted to preparation is much longer. Moreover, the educational value of carefully preparing the music and of becoming acquainted with the techniques of singing and with the aesthetic niceties of style and interpretation should by no means be underestimated. The choir and trainer get to know not only the music but also each other, and the trainer has to use his skills wisely in developing the human and musical resources available to him, in order to realize their greatest potential (Introduction, p. ii-iii)
Keywords: Choral music -- Scores Choral music -- Instruction and study Choirs (Music) -- Instruction and study; Choral singing; Scores; Children's choirs; Choral training